The relation of lamb quality factors to grade, marbling, carcass value and sensory evaluations - Kropf, Donald H.; Mackintosh, D.L.; Menzies, C.S.; Harrison, D.; Anderson, L. (Kansas Agricultural Experiment Station, 2011)
This study was to determine quality factors most closely related to carcass grade, marbling in the rib eye muscle, and to tenderness. A total of 376 crossbred lambs were slaughtered over 4 years at an approximate live weight of 90 lb. after carcasses chilled 48 hours. D.S.D.A. carcass grade and various quality scores were evaluated by a representative of the Federal Meat Grading Service. Carcasses were cut to wholesale cuts and weights obtained. The hotel rack was physically separated into fat, L. dorsi muscle, other lean, intercostal tissue, overflow fat and bone.
Keywords: Lamb; Yield grade; Marbling; Carcass value